Art Music Composition in Malaysia: A Focus on Three Composers - Lam, Ming Huey (2000)
Most researches conducted on Malaysian music thus far concentrates on the area of history and development of traditional music and popular music. There has been a lack of research in art music composed by Malaysian composers trained in the Western art music tradition. The objective of this research is to present the contribution of three Malaysian art music composers and the role they play in the formation of a Malaysian identity in the world of art music composition. This research systematically documents the work of three Malaysian composers, namely, Minni Ang, Chan Cheong Jan and Valerie Ross. These composers were chosen to represent different styles of art music composition in Malaysia. The musical backgrounds of the composers are studied in order to understand the processes that led them to art music composition. A few compositions that reflect their compositional styles are chosen and analysed.The research methodology used in this work begins with the collection of data and information on the background of the composers and their compositions. A few analysis methods are used to analyse the compositions. These include chord analysis, formal analysis, and twelve-tone analysis. The result of this research indicates that the three composers presented in this thesis compose in different styles. Ang uses various composition styles in different works. Chan quotes Malay folk tunes or Malay dance rhythms in his music and presents them in Western classical style. Ross prefers to include traditional instruments in her compositions and composes in cross-cultural fusion style. Although the composition styles of these three composers are different, their aims to assert their own identities in the world of art music composition are similar. As indicated by the three different compositional styles of the above composers, it is assumed that there is yet no common direction or trend that exists in the field of art music composition in Malaysia. As a result, it is still hard to define what stage the development of art music composition in Malaysia is at, today. With the establishment of tertiary programs in music and support from government and private sector, more Malaysian art music is projected to be composed in future, leading to a trend that should slowly emerge in the field of Malaysian art music composition.